2008
DOI: 10.1117/12.772640
|View full text |Cite
|
Sign up to set email alerts
|

EUV pattern shift compensation strategies

Abstract: EUV lithography is one of the hot candidates for the 22nm node. A well known phenomenon in EUV lithography is the impact of non-telecentricity and the mask topography on printing performance. Due to oblique illumination of the mask, layout, the printed features are shifted and biased on the wafer with respect to their target dimension up to several nanometers. This effect is inherent to EUV imaging systems. In order to maintain CDU, overlay and registration requirements, these effects need to be compensated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…[16][17][18][22][23][24][25][26][27][28][29][30][31][32] An X and/or Y translation of the full-chip design relative to the blank is essential, however, additional degrees of freedom can also be considered, such as 90-degree rotations, micro-rotations 30 , and mask floorplanning 22,29 . Previous work have shown that microrotations and floorplanning provides only slight improvements for defect avoidance, despite the considerable complexity and resource allocation needed for HVM implementation.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…[16][17][18][22][23][24][25][26][27][28][29][30][31][32] An X and/or Y translation of the full-chip design relative to the blank is essential, however, additional degrees of freedom can also be considered, such as 90-degree rotations, micro-rotations 30 , and mask floorplanning 22,29 . Previous work have shown that microrotations and floorplanning provides only slight improvements for defect avoidance, despite the considerable complexity and resource allocation needed for HVM implementation.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…Thus, the image formation in EUV projection systems has specific challenges not found in immersion lithography. A number of authors have investigated EUV specific effects such as pattern placement error [1], assist feature placement and resulting Bossung tilt [2] and the stochastic nature of EUV imaging [3]. The recent publication by Hsu et al [4] demonstrated resolution enhancement techniques (RET) to address these EUV specific issues as part of the ASML Brion Tachyon NXE Source Mask Optimization (SMO) application.…”
Section: Introductionmentioning
confidence: 98%
“…5,6 In EUVL systems all of these 3D mask effects are still present [7][8][9][10][11][12] in addition to image placement error due to the oblique illumination. 13,14 Of course the effects of mask topography are not lens aberrations, but drawing analogies to traditional aberration theory informs potential pupil plane compensation strategies.…”
Section: Introductionmentioning
confidence: 98%